Controlling the film structure by regulating 2D Ruddlesden–Popper perovskite formation enthalpy for efficient and stable tri-cation perovskite solar cells - Liang, Chao (2021)
The incorporation of bulky organic cations into metal-halide perovskites, forming 2D–3D heterojunctions, has dramatically improved the stability of perovskite solar cells (PSCs). Nevertheless, the power conversion efficiencies (PCEs) of these PSCs are typically sacrificed because the formed 2D structures possess larger dielectric confinement, wider bandgaps, higher exciton binding energies and lower charge-carrier mobilities than 3D perovskites. Here, we demonstrate that the environmental stability of PSCs could be significantly improved without sacrificing the efficiency by introducing hydrophobic polyfluorinated cations (CF3CF2CH2NH3+, 5F-PA+) to metal-halide perovskites. Due to the large 2D perovskite formation enthalpy with polyfluorinated cations, the addition of such cations will form a protective layer at the grain boundaries of 3D perovskite rather than forming 2D perovskites. The resultant solar cells based on 5F-PA0.05[Cs0.05(MA0.17FA0.83)0.95]0.95Pb(Br0.17I0.83)3 exhibit a substantially increased PCE of 22.86% compared with the control Cs0.05(MA0.17FA0.83)0.95Pb(Br0.17I0.83)3 devices (20.69%). More importantly, the optimized devices could retain 80% of their original PCEs after >3000 h in the ambient environment with a 65 ± 10% relative humidity, which is attributed to the hydrophobic fluorine moieties. This work provides new understanding of the enhancement of PSC stability by incorporating polyfluorinated cations.